Control of Fluoroquinolone Resistance through Successful Regulation, Australia - Allen C. Cheng; John Turnidge; Peter Collignon; David Looke; Mary Barton; Thomas Gottlieb (Emerging Infectious Diseases, 2012)
Fluoroquinolone antimicrobial drugs are highly bioavailable, broad-spectrum agents with activity against gram-negative pathogens, especially those resistant to other classes of antimicrobial drugs. Australia has restricted the use of quinolones in humans through its national pharmaceutical subsidy scheme; and, through regulation, has not permitted the use of quinolones in food-producing animals. As a consequence, resistance to fluoroquinolones in the community has been slow to emerge and has remained at low levels in key pathogens, such as Escherichia coli. In contrast to policies in most other countries, this policy has successfully preserved the utility of this class of antimicrobial drugs for treatment of most infections.